Mediating effect of fear of falling on association between activities of daily living and frailty among rural older adults in Shandong province, China - Ye-min YUAN; Cheng-chao ZHOU; Jie LI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore mediating effect of fear of falling (FoF) on the association between activities of daily living (ADL) and frailty among rural elderly for providing references to frailty prevention in the elderly. MethodsUsing a multistage stratified random sampling method, we conducted a questionnaire survey among 3 600 permanent rural residents aged ≥ 60 years in three counties of Shandong province from May to July 2019. The Frail Scale, 10-Item Kessler Psychological Distress Scale (K10), Mini-Mental State Examination (MMSE), Activities of Daily Living Scale (ADL), and a self-designed questionnaire were adopted in the survey. Statistical analyses were performed on the data collected from 3 242 valid respondents and the RMediation program of R 3.6.1 software was used to evaluate mediating effect of FoF. ResultsFor all the valid respondents, the frailty score was 1.52 ± 1.08, and 18.11% (587), 64.68% (2 097), and 17.21% (558) of the respondents were assessed in the frail, pre-frail, and non-frail condition, respectively. The respondents had an average ADL score of 16.99 ± 4.37, with 87.88% (2 849) and 12.12% (393) having normal and decreased ADL. More than a half of the respondents (58.14%, 1 885) reported FoF. Spearman correlation analysis showed that decreased ADL and FoF were positively associated with frailty (r = 0.265 and r = 0.161, both P < 0.001), and declined ADL was also positively associated with FoF (r = 0.112, P < 0.001). Multivariate logistic regression analysis indicated that decreased ADL could increase the risk of frailty [odds ratio (OR) = 3.06, 95% confidence interval (95% CI): 2.40 - 3.90] and FoF (OR = 1.70, 95% CI: 1.32 - 2.20); FoF was a risk factor for both frailty (OR = 1.37, 95% CI: 1.17 - 1.60) and weakened relationship between ADL and frailty (OR = 2.98, 95% CI: 2.33 - 3.80). The results of mediating effect analysis revealed that FoF played a partial mediation effect on the association between ADL and frailty and the 95% CI was 0.08 - 0.27 for the effect value. ConclusionAmong rural elderly in Shandong province, FoF is a mediator between ADL and frailty and psychological intervention on FoF needs to be promoted among the elderly with decreased ADL for attenuating frail condition of the elderly.